Winter Turf Growing Season Elongation Characteristics of a Thermosyphon Unit that Uses a Shallow Geothermal Source. Issue 7 (17th August 2016) - Zhou, Feng; Ma, Guoyuan; Zhang, Xiaolin
Abstract: Low temperature stress is an important factor for turf growth in the northern high‐latitude environment. A thermosyphon temperature controlling unit with a shallow geothermal source was proposed by analyzing present techniques to prolong the turf growing season in winter. Thermosyphon unit prototypes were developed and tested in a water park. The relations between ambient temperature, depth, material, structure, underground temperature, and root temperature were studied experimentally. The thermosyphon unit performance was analyzed. Results indicate that underground and root temperatures remain almost constant with an hourly ambient temperature. The root temperature remains steady due to the thermosyphon unit application. The underground temperature increases with the depth increase, and the increment is at most 1 °C. The root temperature of a copper thermosyphon unit is higher than that of a steel thermosyphon unit, and the temperature difference can reach 2 °C. The root temperature of a type I thermosyphon unit is higher than that of a type II, and the temperature increase is less than 1 °C. The root temperature variation due to the thermosyphon material is smaller with the increase in depth.